2018
DOI: 10.1016/j.cej.2017.11.128
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of deoxygenation in anisole decomposition over single-metal loaded HZSM-5: Experimental study

Abstract: This work investigates the deoxygenation reaction during the decomposition of anisole (methoxy-rich model compound of lignin) over bi-functional catalyst. The bifunctional catalyst consisted of a single metal loaded on an acid support; the active metals, i.e. Ni, Co, Mo and Cu, were loaded at various rates, and the acid support was HZSM-5 zeolite with a Si/Al ratio of 25 (HZ(25)). Experiments were conducted in a bench-scale fluidised bed reactor within the temperature range from 400˚C to 600˚C. Experimental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 67 publications
2
29
0
Order By: Relevance
“…Our research group has recently reported the conversion of anisole over non-metal HZSM-5 zeolite [10]. Compared to the results previously reported, both the yield and selectivity of BTX have been enhanced by the addition of the bimetallic sites (on average by 20% and 36% respectively) [10,32]. The improvement is attributed to an increment in the conversion of Phs towards BTX, and indicates that the studied supported bimetallic catalysts may promote the deoxygenation of Phs.…”
Section: Effect Of the Type Of Metal Combination On Deoxygenation Reamentioning
confidence: 66%
See 3 more Smart Citations
“…Our research group has recently reported the conversion of anisole over non-metal HZSM-5 zeolite [10]. Compared to the results previously reported, both the yield and selectivity of BTX have been enhanced by the addition of the bimetallic sites (on average by 20% and 36% respectively) [10,32]. The improvement is attributed to an increment in the conversion of Phs towards BTX, and indicates that the studied supported bimetallic catalysts may promote the deoxygenation of Phs.…”
Section: Effect Of the Type Of Metal Combination On Deoxygenation Reamentioning
confidence: 66%
“…This work aims to investigate the deoxygenation reaction in the decomposition of anisole over zeolite supported bimetallic catalysts for the production of the BTX fraction (benzene, toluene, and xylene). Our previous study has reported the excellent performance of 1%Ni/HZ (25) and 1%Mo/HZ (25) in the decomposition of anisole [32], besides, our modelling work also revealed that Ni and Mo led to high adsorption energy in anisole adsorption, and Fe resulted in a low energy adsorption [33]. In this study, combinations of Ni, Mo and Fe active metal sites were evaluated.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Phenol is well known to have a difficult‐to‐cleave C aromatic —OH bond and acts as an HDO inhibitor by strongly adsorbing to the catalyst acid sites . Conversely, anisole's methoxy group can provide insights about the preference of first‐step hydrogenation versus C aromatic —O—CH 3 cleavage via the demethoxylation–demethylation route . Figure shows the conversion and selectivity as a function of TOS for 0.8Rh‐HY‐R.…”
Section: Resultsmentioning
confidence: 99%